STRUCTURAL DESIGN LIQUID BULK DOCK IN WAYAME FUEL OIL TERMINAL AMBON - Ilham Dirgantara, Muhammad
The Wayame Fuel Oil Terminal (TBBM) is one of BBM terminals which has an important role as the backbone in BBM supplying to the Maluku-Papua region. Therefore, one of the fuel oil terminal facilities is a dock as a tanker rests to Wayame TBBM also has an important role. The final project discusses about the dock structural design at Wayame Fuel Oil Terminal (TBBM), Ambon. It is designed by dolphin dock structural that consist of laoding platform, breasting dolphin, mooring dolphin, trestle and catwalk structures. Theres are elemented by beams, plates, pile caps and piles. The scopes discussion of final project are secondary data collection, loading calculation on the structure, determination of structural dimensions and also the elements structural (preliminary design), structural modelling, reinforcement of structural elements, and geotechnical analysis . Structural analysis was performed by using SAP2000 software refers to AISC 360-16 standard code. The results of modeling are unity check ratio (UCR), structural deflection, internal forces, and the structural element placement reaction. The UCR amount of the Structural Design Liquid Bulk Dock is planned between 0.7 to 1.0 by deflection occurs at the pile and beam which does not exceed of the permit deflection limit. The force of structural elements is obtained from the modeling results that used as the basis for reinforcing it. Then, the placement reaction is used to determine the depth of piling by considering of geotechnical analysis at the location. The results of this final project are the structural dimension and structural element of dock structural, ship berthing facilities, details of reinforcement structural dock elements, and depth of piling.